The female in organizations: a management study in the pharmaceutical industry sector - Reis, Maria Cristine dos; Melo, Marlene Catarina de Oliveira Lopes (Revista de Administração da UFSM, 2020)
The objective of this study was to analyze the perception of women in managerial work according to pharmaceutical industry managers based in the cities of São Paulo and Rio de Janeiro operating in the region of Minas Gerais. This is a field study with a qualitative and descriptive approach. A semi-structured interview script was used to collect data, and the subjects of this survey were ten district managers. The results show that the management of people is punctuated as the main activity developed in the exercise of the function. No salary differences were found between men and women in the pharmaceutical companies surveyed. The clothing, that is, the care with the visual, as well as the understanding, sensitivity and care with the people were pointed out as a way to feel feminine in the managerial career. The managerial function was described as unisex and / or asexual and the way of managing is associated to the profile of each one. The availability for trips to the service was pointed out as an ideal activity for the men, but that does not prevent them from exercising the managerial function.